REFORMASI BIROKRASI PELAYANAN KEHUMASAN DI BAGIAN HUMAS DAN PROTOKOL SEKRETARIAT DAERAH KABUPATEN SEMARANG - Barus, Samesnego Brevan; Mustam, Moch. (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Bureaucratic reformation is a transformation process in the governance area in order to achieve the Good Government. One of the area is the public service aiming to establish a qualified and well used service by the society. The society’s fulfillment of public information becomes strategic in this IT era. This research will talk about the achievement of bureaucratic reformation in the Public Relations services that is handled by the Public Relations and Secretariat Protocol in Semarang District and the inhibiting factors. This research uses the Bureaucratic Reformation theory, public service management theory, and society’s participation theory. The technique used to gather data is through observation, interviews, and documented informants which are staff of the Public Relations and Secretariat Protocol in Semarang District. The result of this research has shown that the bureaucratic reformation in public services has not been well done and there were some internal inhibiting factors which are the lack of human resources, the lack of facilities and infrastructures, and two external factors which are the geographical conditions of Semarang District, and the lack of society’s capabalities on Information and Technology. Author’s suggestion is for the Semarang’s dictrict regent to increase his involvement throught budget increases and more surveillance in the execution of bureaucracy reformation in the public relation service. More than that, he may as well enhance more cooperation with investor or private sector in order to make a good community empowerment and civilian state apparatus.